Q. 2 K4.1( 10 Votes )

<span lang="EN-US

Answer :

In the given expression


We know that


(a + b)2 = a2 + 2ab + b2


(a-b)2 = a2-2ab + b2


Hence


If a = x and b = y


(x + y)2 – (x – y)2 = x2 + y2 + 2xy – [x2 + y2-2xy]


= x2 + y2 + 2xy -x2-y2 + 2xy


= 4xy


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
NCERT | Factorisation ProblemsNCERT | Factorisation ProblemsNCERT | Factorisation Problems38 mins
Quiz | Questions on FactorizationQuiz | Questions on FactorizationQuiz | Questions on Factorization41 mins
Quiz | Important Questions on FactorisationQuiz | Important Questions on FactorisationQuiz | Important Questions on Factorisation35 mins
Algebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak Areas41 mins
Champ Quiz | Division of PolynomialsChamp Quiz | Division of PolynomialsChamp Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics